2011
DOI: 10.1189/jlb.0511239
|View full text |Cite
|
Sign up to set email alerts
|

The monomer-dimer equilibrium and glycosaminoglycan interactions of chemokine CXCL8 regulate tissue-specific neutrophil recruitment

Abstract: Chemokines exert their function by binding the GPCR class of receptors on leukocytes and cell surface GAGs in target tissues. Most chemokines reversibly exist as monomers and dimers, but very little is known regarding the molecular mechanisms by which the monomer-dimer equilibrium modulates in vivo function. For the chemokine CXCL8, we recently showed in a mouse lung model that monomers and dimers are active and that the monomer-dimer equilibrium of the WT plays a crucial role in regulating neutrophil recruitm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
108
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
3

Relationship

5
2

Authors

Journals

citations
Cited by 74 publications
(116 citation statements)
references
References 27 publications
3
108
1
Order By: Relevance
“…Our NMR-derived structural model of the murine CXCL1 dimer-octasaccharide complex shows that GAG binds perpendicularly to the C-terminal helices, is consistent with model II, and completely rules out model III. In model III, GAG is nestled between the helices and does not interact with the 3 10 helix, which contradicts our data and also the binding and functional data for human CXCL8 and murine CXCL2 (28,29,49). Our data are also inconsistent with model I but cannot completely rule it out and require structural studies using heparan sulfate GAGs containing both sulfated (NS) and non-sulfated (NA) domains.…”
Section: Discussioncontrasting
confidence: 56%
See 1 more Smart Citation
“…Our NMR-derived structural model of the murine CXCL1 dimer-octasaccharide complex shows that GAG binds perpendicularly to the C-terminal helices, is consistent with model II, and completely rules out model III. In model III, GAG is nestled between the helices and does not interact with the 3 10 helix, which contradicts our data and also the binding and functional data for human CXCL8 and murine CXCL2 (28,29,49). Our data are also inconsistent with model I but cannot completely rule it out and require structural studies using heparan sulfate GAGs containing both sulfated (NS) and non-sulfated (NA) domains.…”
Section: Discussioncontrasting
confidence: 56%
“…NACs reversibly exist as monomers, dimers, and/or tetramers, and recent in vivo studies using disulfide-trapped dimers have shown that dimers are highly efficient in recruiting neutrophils. As dimers have a similar or lower receptor activity, the higher recruitment may be due to GAG interactions (5,28). However, the molecular mechanisms by which GAG interactions mediate recruitment are not known because there is a lack of experimental data on the structural architecture of NAC dimer-GAG complexes.…”
mentioning
confidence: 99%
“…Animal model studies have shown that the ability to reversibly exist as monomers and dimers regulates recruitment (3,4,13). Under conditions of active neutrophil trafficking, the local chemokine concentration could vary by orders of magnitude, and, therefore, in principle, hCXCL1 could exist as monomers, dimers, or both at different times and locations.…”
Section: Discussionmentioning
confidence: 99%
“…A series of HSQC spectra was collected on titrating dp8 and dp14 until essentially no changes in chemical shifts were observed. We used heparin oligosaccharides because they are nearly fully sulfated, are available commercially, and have been shown to capture endogenous interactions (4). Considering that hCXCL1 exists as monomers and dimers (monomer-dimer equilibrium constant, ϳ4 M), we initially characterized binding at low concentrations.…”
Section: Characterization Of Gag-hcxcl1mentioning
confidence: 99%
See 1 more Smart Citation